Does Bacterial Elasticity Affect Adhesion to Polymer Fibers? - Melo-Hurtado, F; Hamm-Hahn, L; Caballero-Alvial, L (American Chemical Society, 2020)
The factors governing bacterial adhesion to substrates with different topographies are still not fully identified. The present work seeks to elucidate for the first time and with quantitative data the roles of bacterial elasticity and shape and substrate topography in bacterial adhesion. With this aim, populations of three bacterial species, P. aeruginosa DSM 22644, B. subtilis DSM 10, and S. aureus DSM 20231 adhered on flat substrates covered with electrospun polycaprolactone fibers of different diameters ranging from 0.4 to 5.5 μm are counted. Populations of bacterial cells are classified according to the preferred binding sites of the bacteria to the substrate. The colloidal probe technique was used to assess the stiffness of the bacteria and bacteria-polymer surface adhesion energy. A theoretical model is developed to interpret the observed populations in terms of a balance between stiffness and adhesion energy of the bacteria. The model, which also incorporates the radius of the fiber and the size and shape of the bacteria, predicts increased adhesion for a low level of stiffness and for a larger number of available bacteria-fiber contact points. Te adhesive propensity of bacteria depends in a nontrivial way on the radius of the fibers due to the random arrangement of fibers. © 2020 American Chemical Society.